Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð½Ð¸Ð·ÐºÐ¾Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ð¾Ð³Ð¾ ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð±ÐµÐ· ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð° Ð¸ Ð¿Ð¾Ð´ Ð·Ð°Ñ‰Ð¸Ñ‚Ð¾Ð¹ Me2SO Ð½Ð° Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ Ð¾ÐºÐ¸ÑÐ»Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾-Ð²Ð¾ÑÑÑ‚Ð°Ð½Ð¾Ð²Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ñ‹Ñ… Ñ„ÐµÑ€Ð¼ÐµÐ½Ñ‚Ð¾Ð² Ð² Ñ‚ÐºÐ°Ð½Ð¸ Ð¿Ð»Ð°Ñ†ÐµÐ½Ñ‚Ñ‹ - Yurchenko, T. N.; Belonozhko, A. P.; Zhulikova, E. P.; Sharlaj, T. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
Using the methods of quantitative histochemistry and quantitative photometric analysis there was carried-out the investigation of change in SDG, LDG, Î±-GPhDG, NAD.H2 and NADP.H2 activity in placenta tissue after its low temperature preservation without cryoprotectant and after treatment with Me2SO cryoprotectant solution.